Frugal Innovation: A Bibliometric Study of the Conceptual Foundations and Future Research Directions - Kawuryan Renita; Prapdopo; Andi Nurhasanah (Faculty of Economics and Business Udayana University, 2025)
Frugal innovation is gaining traction in resource-limited settings, emphasizing sustainability. This paper uses bibliometric analysis to explore trends and gaps in frugal innovation research. Further publications were identified from the Scopus database using the Publish or Perish tool for the period 2014-2024. Data is processed using RStudio and VOSviewer to reveal key themes, influential scholars, research institutions, and network maps. It highlights the growing scholarly interest in frugal innovation and its alignment with sustainability goals, stressing the need for further exploration of its principles and impacts. The study aims to advance understanding and to guide future research. Additionally, integrating sustainability and environmental considerations in product development, alongside frugal innovation, can drive economic and social sustainable development. Organizational capabilities like Big Data are vital for achieving sustainability outcomes, and frugal innovation positively impacts a firm's financial and environmental performance. Strengthening organizational capabilities is key to leveraging frugal innovation for sustainability.